Myoma-Related Altered Tubal Anatomy as an Etiologic Factor in Recurrent Ectopic Pregnancy and Infertility: A Case Report - Bayu Pratama Putra; Ika Azdah Murnita (UMI Medical Journal, 2025)
Background: Recurrent ectopic pregnancy remains a significant and complex challenge in obstetric care, particularly when accompanied by comorbid conditions such as uterine myomas. Case Description: We report the case of a 30-year-old woman with a history of two ectopic pregnancies—one involving the right fallopian tube and the other the left—along with a large subserosal uterine myoma. Diagnosis was established via transvaginal ultrasonography and supporting laboratory investigations. The patient underwent a laparotomy with salpingotomy and myomectomy in an effort to preserve reproductive capacity. Timely surgical intervention and comprehensive postoperative management resulted in favorable clinical outcomes, preventing complications and supporting recovery. Conclusion: This case underscores the critical importance of individualized clinical management and interdisciplinary collaboration in addressing complex gynecologic presentations. Further studies are warranted to elucidate the interplay between uterine myomas and ectopic pregnancy and to assess their long-term impact on fertility. Development of more refined diagnostic and therapeutic protocols may contribute to improved maternal outcomes and reproductive preservation.